Ejecta Thickness Distribution of the Schrödinger Basin on the Moon. Issue 12 (10th December 2020) - Xu, Luyuan; Xie, Minggang
Abstract: Thickness distribution of impact ejecta gives insights into the processes of impact cratering, the stratigraphy of planetary crust, future sampling site selection, and the source of lunar samples. In this study, we conduct detailed measurements of ejecta deposit thicknesses for the Schrödinger basin, the second youngest and the best‐preserved peak‐ring impact basin on the Moon. Based on Lunar Reconnaissance Orbiter Camera Wide Angle Camera, Kaguya Terrain Camera, and the Lunar Orbiter Laser Altimeter data, the thicknesses of ejecta deposits are estimated from the measurements of partially filled pre‐Schrödinger craters by using crater morphometry, and the effect of crater degradation is taken into considerations. The thickness distribution of ejecta is derived from the measured thicknesses of ejecta deposits using an updated ballistic sedimentation model. Our measurements yield an ejecta thickness of ∼704 m at the current Schrödinger basin rim under the decay with a power‐law index of −3.0. Based on these measurements, we find that the model of Pike (1974, https://doi.org/10.1016/0012-821x(74)90114-9 ) provides the best estimates of transient cavity rim radius of 95.5 km and excavation depth of 19.6 km for the Schrödinger basin, whereas the widely used model of McGetchin et al. (1973, https://doi.org/10.1016/0012-821x(73)90162-3 ) significantly underestimate the ejecta thickness of Schrödinger basin. In addition, our results indicate that the Schrödinger basin‐forming impact does not penetrate through the lunar crust. Plain Language Summary: A hypervelocity impact on a solid planetary surface forms an impact crater, and a fraction of debris is ejected and emplaced ballistically around the crater. Local materials are excavated by and mixed with ballistically transported ejecta that bombards a target surface; the mixture of ejecta and excavated local materials constitutes ejecta deposits. Clarifying the thickness distribution of impact ejecta gives insights into the process of impact cratering, the stratigraphy of planetary crust, future sampling site selection, and the source of lunar samples. With the assistance of high‐resolution images and topography data, we estimate the thickness distribution of the Schrödinger ejecta by measuring the thicknesses of the Schrödinger ejecta deposits. These results show that previous models tend to substantially underestimate the thickness of the Schrödinger ejecta. In addition, the penetration depth of the Schrödinger impact is too shallow to penetrate through the lunar crust. Key Points: Morphometric measurements of pre‐Schrödinger craters give estimates of ejecta thickness distribution of the Schrödinger basin The ejecta distribution of the Schrödinger basin is inconsistent with the most widely used model of McGetchin et al. (1973) The Schrödinger impact event does not penetrate through the lunar crust